THE EFFECT OF MODIFIED FREE INQUIRY APPROACH ON STUDENT’S PROCESS SKILL AND SCIENCE ATTITUDES - Kholilurrohman Kholilurrohman; I Gusti Putu Suryadarma (Universitas Negeri Yogyakarta, 2019)
This study aims to determine the effect of Modified Free Inquiry approach on student’s process skill, and student science attitudes. This Quasi-Experimental study used pretest-posttest with nonequivalent control group design with grade XI student’s of MAN Maguwoharjo Yogyakarta in the second semester of academic year 2012/2013 as a population, and used 2 classes of XI Science Programs as a sample group. This approach is implemented on biology learning through human sense system matters. Learning in this study lasted for 6 times meetings for each group of samples, and the data were obtained by data collection instruments in the forms of a written multiple choice test for science process skill, observation sheets for scientific process skills and science attitudes, and a questionnaire for science attitudes which was administered before and after learning. The data were processed with IBM SPSS 20 software for windows, and hypothesis testing was done through multivariate analysis. The results of the study show a significant value of 0.000, which mean there are significant effect of Modified Free Inquiry approach on: (1) Student’s science process skill, and (2) science attitudes, if it’s compared with Guided Inquiry approach.